Breaking Away from Progressive History: The Past and Politics in American Studies - Ari Helo (European Journal of American Studies)
This article suggests that, contrary to a widely shared view among American scholars, a progressive view of history is neither essential nor helpful to historical research in American studies—or in any other academic field.